(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Unmanned Arial Vehicle (UAV) Network is an autonomous wireless communication network, mainly used for natural disaster recovery operations to forward the captured images or video information to the ground vehicle. The UAV network can be applied in various applications essentially, search and rescue operations. This work concentrates on Delay Tolerant Network DTN based Decentralized Multi-layer UAV ad-hoc network assisting VANET for post-disaster scenarios. Because of unbalanced links in highly dynamic UAV networks, packet forwarding is a challenge. This work proposes a Binary Spray and wait routing protocol (BSnW) with controlled replication for DTN based Decentralized Multi-layer UAV networks. The Next Layer UAVs are presented to empower a well-organized Store and carry forward (SCF), in Multi-Layer UAV ad-hoc networks. Next Layer UAVs expands the accessibility of connecting tracks among the all DTN UAVs and the ground vehicle, hence reducing end-to-end delays and growing the packet delivery ratio and drop the packet drop ratio. The proposed BSnW with controlled replication protocol enables a high packet delivery ratio, which enables, and guarantees single-copy data forwarding to evade duplication of every message. Proposed protocol has been experimented using Opportunistic Network Environment (ONE) Simulator. Our simulated experiment show that the proposed protocol outstrips the epidemic routing protocols reported in the literature in terms of the packet delivery ratio, average delay, throughput and the routing overhead.